2023
DOI: 10.1124/jpet.122.001563
|View full text |Cite
|
Sign up to set email alerts
|

Beyond VEGF: Targeting Inflammation and Other Pathways for Treatment of Retinal Disease

Abstract: Downloaded fromassociated protein kinase; ROP, retinopathy of prematurity; ROS, reactive oxygen species; RPE, retinal pigment epithelium; RUNX1, runt-related transcription factor 1; sEH, soluble epoxide hydrolase; SDF-1, stromal derived factor-1; shRNA, small hairpin RNA; STAT3, signal transducer and activator of transcription 3; t-AUCB, trans-4-(4-(3adamantan-1-yl-ureido)-cyclohexyloxy)-benzoic acid; TF, transcription factor; Tff1, trefoil factor family 1; TGF-β2, transforming growth factor-β2; TNF-α, tumor n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 142 publications
0
6
0
Order By: Relevance
“…Moreover, as our understanding of the molecular mechanisms underlying various retinopathies increases and the pivotal role played by mitochondria in most oxidative stress-derived ophthalmic pathologies becomes evident, new targets come to the attention of scientists working on the development of novel and more effective therapeutic drugs [ 129 ]. These drugs could be directly developed and formulated for delivery through topical nanotechnological methods [ 130 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, as our understanding of the molecular mechanisms underlying various retinopathies increases and the pivotal role played by mitochondria in most oxidative stress-derived ophthalmic pathologies becomes evident, new targets come to the attention of scientists working on the development of novel and more effective therapeutic drugs [ 129 ]. These drugs could be directly developed and formulated for delivery through topical nanotechnological methods [ 130 ].…”
Section: Discussionmentioning
confidence: 99%
“…The role of canonical VEGF/VEGFR signaling in the context of HHcy-induced endothelial migration and proliferation impairment are contradictory [26][27][28]. Though the suppression of canonical VEGF signaling has been mostly implicated in angiogenic defects and endothelial dysfunction, several independent angiogenic factors [68] as well as alternative mechanisms beyond VEGF signaling are gaining immense importance recently in this regard [32,69,70]. In our sub-lethal Hcy treated endothelial cells we found that the transcript levels of canonical VEGF/VEGFR signaling markers are not reduced.…”
Section: Discussionmentioning
confidence: 99%
“…As NV driven by VEGF-A is responsible for the blindness that occurs with AMD and DR [ 3 , 5 ], clinical trials of the most widely-used anti-VEGF therapeutics, as well as comparative studies among them, have regarded visual gains as an accepted metric of therapeutic efficacy [ 5 , 35 ]. However, being multifactorial disorders [ 43 ], increasing attention is being paid to the overarching influence of pathological processes like inflammation [ 5 , 9 ], including the effects the interplay between pathophysiological conditions, VEGFR1 ligands, pro-inflammatory factors, and the cells from which they originate, have upon the pathogenesis and progression of AMD and DR [ 7 , 9 , 44 , 45 ]. In fact, the effects of inflammation are such that research is currently being pursued on a number of anti-inflammatory therapeutics with novel targets acting via non-VEGF pathways [ 43 ].…”
Section: Discussionmentioning
confidence: 99%